The media economy - Albarran, Alan B. (Media management and economics series)
The Media Economy analyzes the media industries and their activities from macro- to micro-levels, using concepts and theories to demonstrate the role the media plays in the economy as a whole. Representing a rapidly changing and evolving environment, this text breaks new ground through its analysis from two unique perspectives: